American Foreign Policy Towards the Colonels' Greece Uncertain Allies and the 1967 Coup d'État - Karakatsanis, Neovi M. (Palgrave Macmillan US, 2018)
This book seeks to comprehensively analyze and document U.S. foreign policy toward a strategic Cold War ally that posed a stark challenge to the traditionally-stated U.S. preference for democracy and political freedom. It details the complex ways in which the U.S. reacted to that challenge and went about crafting policies of longer-term accommodation with a regime it wished to retain as a close ally in a strategically important part of the world.